Guidelines for kangaroo care in district hospitals and primary healthcare maternity sections in the Free State - Hanneke Dippenaar; Gina Joubert; Maryn E. Brussow (South African Family Practice)
Background: Kangaroo care was introduced in Bogotá, Colombia in 1979 by Dr Edgar Ray and Dr Hector Martinez due to the shortage of resources and the large number of premature babies that needed special care. Kangaroo care implies direct skin-to-skin contact between the mother and her premature/newborn baby. The advantages of kangaroo care are well known and have been published widely. In the National District Hospital in Bloemfontein, South Africa, stable babies are admitted from 1.2 kg and above and the babies are discharged at around 1.8 kg, when they are able to drink adequately. Babies above 1.2 kg are given kangaroo care by their mothers in the day, but sleep in an incubator at night. Babies with a weight of between 1.5 kg and 1.6 kg are started with around-the-clock kangaroo care. The aim of this study was to determine predictors for good and poor outcomes in kangaroo mother care practiced at the primary healthcare level. This information was then used to compile a protocol for kangaroo care in hospitals and maternity sections at the primary care level. The aim of the protocol is to provide specific inclusion and exclusion criteria for kangaroo care, to indicate all the absolute and relative needs for such a unit, to provide guidelines for managing babies with insufficient weight gain, and to provide guidance for follow-up.